Peran Kualitas Audit dalam Memoderasi Pengaruh Kepemilikan Institusional dan Ukuran Perusahaan Terhadap Audit Delay - Sita Sri Nurhayati; Laras Pratiwi; Amalia Siti Khodijah (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This study aims to analyze the effect of institutional ownership and firm size on auditdelay with audit quality as a moderating variable in 54 mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Using a quantitative approach with panel regression analysis, The audit delay is calculated using the number of days between the end of the financial year and issuance date of the audited financial statements; Institutionelles Eigentum is calculated by percentage institutional shareholding; firm size by the natural logarithm of total assets; and audit quality is proxied by the reputation of the Public Accounting Firm (Big Four and Non-Big Four). The results show that institutional ownership has no effect on audit delay, firm size has a negative effect on audit delay, and audit quality weakens the negative effect of both institutional ownership and firm size on audit delay. These findings highlight the need for companies and auditors to reconsider the effectiveness of monitoring mechanisms and audit quality to achieve more optimal audit completion.